Indicators of landscape organization and functionality in semi-arid former agricultural lands under a passive restoration management over two periods of abandonment. (July 2016) - Tabeni, Solana; Yannelli, Florencia A.; Vezzani, Nazareth; Mastrantonio, Leandro E.
Graphical abstract: Highlights: Land abandonment allows to explore the recovery of structure and functions. Landscape functional indicators are used to characterize the passive recovery. Long time abandonment promotes recovery of plant cover and patch structure. Recovery of plant patches increased stability, infiltration and nutrients functions. Abstract: Abandoned lands previously used for agricultural purposes may constitute an opportunity for understanding the variables involved in the restoration of native ecosystems over time. In this study, we assessed the functional status of an abandoned farmland currently used for conservation, using a methodology based on indicators of landscape organization and soil surface. We analyzed changes in plant cover, patch and interpatches structure and several soil surface properties during two periods of land abandonment (less and more than 40 years). Using this methodology, we characterize the potential of the ecosystem to capture and transfer resources, and the state of functional properties such as infiltration capacity, soil stability and nutrient cycling. We detected a significant development of the shrub layer and an increase of the number, type and area occupied by vegetated patches in old fields. The contribution of vegetated patches to the recovery of stability, infiltration and nutrient functions was significant at the local scale. Nonetheless, when analyzing the landscape as a whole only the nutrient cycling index was significantly higher in old fields. The lack of improvement of the stability and infiltration in old fields can lead to further degradation and indicates that even though vegetation cover may have improved over time in old fields, the current cover might not be enough to prevent further degradation by erosion. Our results reinforce the importance of using functionality indexes in future studies focused on adequate restoration measures to protect the function of desert ecosystems, especially when aimed for biodiversity conservation. Hence, the use of monitoring systems based on organization and function indicators is a useful tool to represent the current state and potential recovery of previously disturbed ecosystems, provided that the time scale is taken into account.